Para além da fidelidade na adaptação audiovisual: o caso da minissérie televisiva Capitu - Bulhões, Marcelo [UNESP] (My University, 2012)
Despite the theoretical advances that have discredited the notion of “faithfulness” regarding the adaptation as an intermediatic phenomenon, it still insists on coming up. Capitu, a mini-series shown by the Rede Globo network has been regarded as “unfaithful” to the novel Dom Casmurro. It is a perfect example for this article of the perception of the audiovisual language resources that work as valid analogies to Machado de Assis’ novel, indicating the misconception that underlies the notion of “faithfulness”.

A despeito de avanços teóricos que puseram em descrédito a noção de “fidelidade”, adaptação como fenômeno intermidiático, ela teima em comparecer. Capitu, minissérie exibida pela Rede Globo e apontada como “infiel” em relação ao romance Dom Casmurro, serve a este artigo como caso exemplar à percepção de expedientes da linguagem audiovisual que funcionam como analogias válidas ao romance de Machado de Assis, apontando para o equívoco que subjaz à noção de “fidelidade”.
Beyond faithfulness on audiovisual adaptation: the case of Capitu TV series
Keywords: Adaptation; Audiovisual; Television; Adaptação; Audiovisual; Televisão